The influence of Agile methodology on digital transformation: the case of the South African bank - Daya, Mayur (My University, 2021)
This study aimed to analyse the digital maturity level and understand the influence the Agile methodology has on digital transformation at Bank X. A quantitative study was conducted using primary data with a sample of 123 respondents that attempted the survey. Only 82 respondents successfully completed all four sections of the research instrument. An online survey, consisting of 165 questions, adopted a Likert scoring scale to capture the respondents' feedback. Linear regression, Spearman's Rho, descriptive statistical analysis, the Mann-Whitney test, the correlation test, and the Wilcoxon Signed-Rank test were used to analyse the data. The study found that no statistical differences were observed in the view of the impact of agile on digital transformation between the management and non-management groups. A positive correlation between Agile and digital transformation indicated that an increase in the Agile construct has an increasing effect on the digital transformation construct, confirming that Agile influences digital transformation. A further finding was that both Agile and digital maturity statistically significantly predicted the department's digital transformation. Finally, the Wilcoxon Signed-Ranks test indicated that respondents felt that the department's digital maturity level was higher than the hypothesised maturity level, Stage 3. Based on the digital maturity matrix in Appendix B, the maturity level was less than Stage 4; hence, a maturity level of Stage 3 has been assumed. The study verified that the department has adopted an Agile methodology; however, to attain an elevated digital maturity level, it is recommended that data still needs to be used efficiently to obtain valuable insights for targeted marketing, decision making and the generation of new value streams. It is further recommended that business processes are continuously reviewed, and management needs to be encouraged to take risks that do not have any associated reputational risks. The study's results are significant as they could assist the leadership team to achieve an enhanced digital maturity level with each Agile iteration
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business, 2021
Keywords: Agile; Digital transformation; Digital maturity; SDG-8: Decent work and economic growth